Slow-release coated heat-curable powder coating catalyst composition, powder coating and preparation method thereof

Through the sustained release coatable heat-curable powder coating catalyst composition, the coating and separation of catalysts is achieved by using the difference in molecular polarity and melting point, and the problem of traditional catalysts being easily involved in pre-reaction and short shelf life at room temperature is solved, and the problem of traditional catalysts being easily involved in pre-reaction and short storage period is achieved. Low temperature curing and long storage time effect.

CN119410183AActive Publication Date: 2025-02-11ALCO NEW MATERIALS (FOSHAN) CO LTD +1

Patent Information

Application Number
CN202510009854.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-02-11
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Existing heat-curing powder coating catalysts are prone to pre-reactions at room temperature, resulting in short storage periods. Traditional low-temperature heat-curable epoxy/polyester mixed powder coatings require freezing storage, and it is difficult to adapt to the thermosetting type of coated capsule catalysts. Process requirements for powder coatings.

Method used

Using a sustained release coated heat-curable powder coating catalyst composition, including a core-coated component A (alkaline catalyst), a shell-coated component B (crystalline solid unsaturated polyester resin or semi-crystalline solid Unsaturated polyester resin) and the C component (alkane wax) of the coating medium are coated and separated by molecular polarity and melting point differences, ensuring that the catalyst is stable at low temperature until it is close to the melting point of the packaging material.

Benefits of technology

It achieves ultra-low temperature curing, with a curing temperature as low as 90-120℃, extending the storage time of low-temperature powder coatings, good stability, suitable for large-scale industrial applications, and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410183A_ABST
    Figure CN119410183A_ABST
Patent Text Reader

Abstract

The invention relates to the field of powder coatings, and particularly discloses a slow-release coated heat-curable powder coating catalyst composition, a powder coating and a preparation method of the powder coating. The slow-release coated heat-curable powder coating catalyst composition comprises: i) a component A, which is an inner core coated object and comprises at least one basic catalyst capable of promoting the ring-opening reaction of epoxy resin, and i) a component B, which is an outer core coated object and comprises at least one basic catalyst capable of promoting the ring-opening reaction of epoxy resin; ii) a component B, which is a coated shell comprising at least one crystalline solid unsaturated polyester resin or a semi-crystalline solid unsaturated polyester resin; the component C is a coating medium and comprises at least one alkane wax.The low-temperature powder coating can be cured at the ultralow temperature, the curing temperature is as low as 90-120 DEG C, the storage time of the low-temperature powder coating is effectively prolonged, and the requirement of a normal powder coating process is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder coatings, and in particular to a slow-release coated heat-curable powder coating catalyst composition, a powder coating and a preparation method thereof. Background Art

[0002] Since powder coatings do not use organic solvents found in traditional solvent-based coatings, they emit almost no VOCs to the atmosphere and are therefore environmentally friendly coatings. At the same time, oversprayed powder coatings can be recycled with an efficiency of nearly 100%, eliminating the difficulty in recycling and treating solid hazardous waste generated by overspray of liquid coatings. Therefore, powder coatings have been vigorously developed as a green and environmentally friendly coating for source control of air pollution and solid hazardous waste.

[0003] Powder coatings can be thermosetting or thermoplastic, and the present invention relates to the field of catalysts for thermosetting powder coatings. Thermosetting powder coatings refer to a mixture of multiple components that has the ability to form an irreversible crosslinked network after thermal curing without the need for a thermal free radical initiator to initiate free radicals.

[0004] Since the 1990s, people have been continuously studying the application of powder coatings on heat-sensitive substrates such as wood and plastic. The earliest method was to use UV radiation to cure powder coatings on the wood surface, heating and leveling at 100-130°C for 3-5 minutes, and then curing them under UV radiation to form a coating. However, for powder coatings with high coloring requirements, UV radiation is difficult to penetrate, resulting in uneven curing of the powder coating, and UV radiation is also prone to yellowing the coating color; radiation curing cannot be achieved on complex 3D workpieces, so UV-curable powder coatings have not been used on a large scale in commercial applications for more than 30 years.

[0005] Under catalyst-promoting conditions, the traditional thermosetting polyester-epoxy hybrid system or thermal free radical initiation can achieve thermal curing at 110-150°C. Powder industry technicians are familiar with the fact that traditional low-temperature heat-curable epoxy / polyester hybrid powder coatings below 120°C require the addition of more amine or onium salt catalysts, which belong to the ionic epoxy group ring-opening polymerization mechanism. When the powder coating is stored at room temperature of 23°C, the epoxy group ring-opening reaction will partially occur, causing the powder coating coating to lose gloss, and serious pre-reaction phenomena such as sanding and non-curing will occur. Traditional low-temperature heat-curable epoxy / polyester hybrid powder coatings need to be stored under refrigerated conditions of 4-20°C, with a shelf life of no more than 15 days. They are prone to lose gloss and failure at room temperature, making it difficult to recycle the powder coating under normal coating processes at room temperature of 23-40°C.

[0006] In order to solve the problem of pre-reaction of ultra-low temperature powder coatings during storage at room temperature and short storage period caused by excessive addition of catalyst, technical personnel have developed latent or coated catalysts. However, the latent decapsulation temperatures currently developed are very high, all above 130°C. Coated capsule catalysts are difficult to meet the process requirements of melt extrusion and crushing of thermosetting powder coatings. In addition, the packaging materials used for coating cannot participate in the chemical reaction of the powder coating, and the packaging material residues have a relatively large impact on the coating performance. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a slow-release coated heat-curable powder coating catalyst composition and a preparation method thereof, which can achieve ultra-low temperature curing with a curing temperature as low as 90-120°C and effectively prolong the storage time of the low-temperature powder coating.

[0008] The technical problem to be solved by the present invention is also to provide a slow-release coated heat-curable powder coating catalyst composition and a preparation method thereof, wherein the catalyst is isolated from the main reaction components at room temperature, cannot participate in the chemical cross-linking reaction, and has good stability.

[0009] The technical problem to be solved by the present invention is also to provide a slow-release coated heat-curable powder coating catalyst composition and a preparation method thereof, which can be desealed and activated at a low temperature of 90°C, close to the melting point of the packaging material, and catalyze the main chemical reaction of the ultra-low temperature powder coating at a temperature of 95-120°C.

[0010] The technical problem to be solved by the present invention is also to provide a slow-release coated heat-curable powder coating catalyst composition and a preparation method thereof. After the catalyst is melt-activated, the packaging material used for the coated catalyst is itself one of the main reaction resin components of the powder coating and can participate in the chemical cross-linking reaction to form a cured coating.

[0011] The technical problem to be solved by the present invention is also to provide a heat-curable powder coating and a preparation method thereof, which can achieve low-temperature curing, long storage time, good stability, large-scale industrial application, and low cost.

[0012] In order to achieve the above technical effects, the present invention provides a slow-release coated heat-curable powder coating catalyst composition, comprising: i) Component A, wherein the component A is a core coating, and comprises at least one alkaline catalyst capable of promoting the ring-opening reaction of the epoxy resin; ii) a B component, wherein the B component is a coating shell comprising at least one crystalline solid unsaturated polyester resin or a semi-crystalline solid unsaturated polyester resin; iii) a C component, wherein the C component is a coating medium comprising at least one alkane wax.

[0013] As an improvement of the above solution, the A component contains at least one alkaline catalyst that can promote the ring-opening reaction of the epoxy resin at 70-130°C.

[0014] As an improvement of the above solution, the component A contains at least one organic amine catalyst, organic phosphorus salt catalyst or imidazole catalyst that can promote the ring-opening reaction of epoxy resin.

[0015] As an improvement of the above solution, the A component contains at least one anionic copolymerization Lewis base catalyst that can promote the ring-opening reaction of the epoxy resin.

[0016] As an improvement of the above solution, the component A contains at least one organic onium salt catalyst that can promote the ring-opening reaction of epoxy resin.

[0017] As an improvement of the above solution, the average particle size of the A component is 0.8-1.5 microns.

[0018] As an improvement of the above solution, the B component is a product of a reaction between a crystalline polyester or a semi-crystalline polyester containing a carboxyl group and a methacrylic acid monomer and / or a derivative thereof.

[0019] As an improvement of the above scheme, the B component satisfies at least one of the following conditions: a. The number average molecular weight Mn of the B component is 100-10000Da; b. The melting point of the B component is 50-120°C and the crystallization point is 40-90°C; c. The viscosity of the B component at a temperature of 100° C. is 0.01-20 Pa.s.

[0020] As an improvement of the above solution, the C component contains at least one straight-chain alkane paraffin.

[0021] As an improvement of the above scheme, the C component contains at least one alkane wax containing 15 to 35 carbon atoms.

[0022] As an improvement of the above scheme, the C component contains at least one alkane wax having a melting point of 30-70°C.

[0023] As an improvement of the above scheme, the sum of the added amounts of component A, component B and component C is 100wt%; The amount of component A added is 20-60wt% of the total amount of component A, component B and component C; The amount of component B added is 30-70wt% of the total amount of component A, component B and component C; The added amount of the C component is 10-45 wt % of the total amount of the A component, the B component and the C component.

[0024] Correspondingly, the present invention also discloses a method for preparing a slow-release coated heat-curable powder coating catalyst composition, comprising: Heat component C to make it melt completely and turn it into a liquid state; Crush component A; Adding the crushed component A to the liquid component C, stirring and mixing evenly to obtain a first premix; The first premix is ​​heated to a temperature above the melting point of component B, component B is added to the first premix, and stirred to completely melt component B to obtain a second premix; The second premix is ​​cooled and stirred at a low speed until the C component forms two distinct layers, the upper phase is the separate C component, and the lower phase is the mixed phase of the B component covering the A component; The upper phase is sucked out, cooled and crushed; The lower phase is pulverized to obtain a slow-release coated heat-curable powder coating catalyst composition.

[0025] As an improvement of the above scheme, the C component is heated to T1, and the melting point of the C component is T C , T1-T C =2℃~8℃.

[0026] As an improvement of the above solution, component A is crushed to an average particle size of 0.1-5 microns.

[0027] As an improvement of the above solution, component A is crushed to an average particle size of 0.8-1.5 microns.

[0028] As an improvement of the above scheme, the first premix is ​​heated to T2, and the melting point of the B component is T B , T2-T B =12℃~20℃.

[0029] As an improvement of the above scheme, the second premix is ​​cooled to T3, and the melting point of the B component is T B , the melting point of the C component is T C , T3-T C =2℃~8℃, and T B -T3=12℃~20℃.

[0030] As an improvement of the above solution, the lower phase is crushed to an average particle size of 0.5-5 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

[0031] As an improvement of the above solution, the lower phase is crushed to an average particle size of 1-3 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

[0032] Correspondingly, the present invention also provides a heat-curable powder coating, comprising the above-mentioned slow-release coated heat-curable powder coating catalyst composition; or, the slow-release coated heat-curable powder coating catalyst composition prepared by the above-mentioned preparation method.

[0033] As an improvement of the above solution, it also includes resin, and the resin is selected from one or more of epoxy resin and polyester resin.

[0034] As an improvement of the above scheme, the addition amount of the slow-release coated heat-curable powder coating catalyst composition is 1wt%-20wt%; The added amount of the resin is 80wt%-99wt%.

[0035] As an improvement of the above solution, it also includes one or more of fillers, pigments, and additives.

[0036] Accordingly, the present invention also provides a method for preparing a heat-curable powder coating, comprising: Mixing a resin and a slow-release coated heat-curable powder coating catalyst composition to obtain a powder coating preliminary mixture; Melting and mixing the powder coating preliminary mixture, and cooling to room temperature to obtain a mixture; The cooled mixture is pulverized to obtain a powder coating.

[0037] As an improvement of the above solution, the powder coating premix is ​​melt-mixed including: The powder coating preliminary mixture is melt-extruded through an extruder.

[0038] The implementation of the present invention has the following beneficial effects: 1. The slow-release coated heat-curable powder coating catalyst composition of the present invention comprises component A, component B and component C, wherein component A is a core coating, which comprises at least one alkaline catalyst that can promote the ring-opening reaction of epoxy resin; component B is a coating shell, which comprises at least one crystalline solid unsaturated polyester resin or semi-crystalline solid unsaturated polyester resin; component C is a coating medium, which comprises at least one alkane wax.

[0039] Among them, (1) Component A is the core coating, which contains at least one alkaline catalyst that can promote the ring-opening reaction of epoxy resin. The molecular polarity difference between the coating medium alkane wax of component C and the (semi-) crystalline solid polyester resin of component B is used to make the two completely insoluble, so that component B can be suspended and dispersed in the coating medium of component C, and the basic conditions required for coating are achieved. Then, the melting point temperature difference between the coating medium alkane wax of component C and the (semi-) crystalline solid polyester resin of component B is used to separate them into two obvious phases, thereby achieving the purpose of coating and separation.

[0040] (2) The catalyst composition of the present invention is applied to powder coatings to achieve ultra-low temperature curing, with the curing temperature as low as 90-120°C. Moreover, it can effectively extend the storage time of low-temperature powder coatings from the original 7 days to more than 30 days at room temperature, meeting the requirements of normal powder coating processes.

[0041] (3) The catalyst coated with a packaging material with a melting point higher than 50°C at room temperature is isolated from the main components of the reaction and cannot participate in the chemical cross-linking reaction, thus having good stability.

[0042] (4) The catalyst composition of the present invention is decapsulated and activated at a low temperature close to the melting point of the packaging material at 90°C, and catalyzes the main chemical reaction of the ultra-low temperature powder coating at a temperature of 95-120°C.

[0043] (5) After the catalyst composition of the present invention is melt-activated, the packaging material used to coat the catalyst is itself one of the main reaction resin components of the powder coating and can participate in the chemical cross-linking reaction to form a cured coating.

[0044] (6) The coating medium C component of the catalyst composition of the present invention is easy to separate and can be recycled and reused. The coating process is green and environmentally friendly, and no three wastes are generated. This solves the problems of the conventional coating technology, such as the complex separation of the coating medium, the difficulty in reuse, and the easy generation of wastewater and harmful organic matter.

[0045] 2. The method for preparing the sustained-release coated heat-curable powder coating catalyst composition of the present invention is simple, highly operable, and easy to control, and can obtain a powder coating catalyst composition with good quality and stability.

[0046] 3. After the powder coating of the present invention is thermally cured, a powder coating with well-balanced properties such as leveling, adhesion, flexibility and hardness is obtained, and it has a high degree of colorability. It can be applied to non-heat-sensitive or heat-sensitive materials such as metal, wood, plastic, calcium silicate, and even 3D complex workpieces. It has a wide range of applications and good decorative effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 is a differential scanning calorimetry (DSC) graph of the heat-curable powder coating of the present invention.

[0048] Figure 2 The present invention is a flow chart of a method for preparing a heat-curable powder coating catalyst composition. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in further detail below.

[0050] The present invention provides a slow-release coated heat-curable powder coating catalyst composition, comprising: i) Component A, wherein the component A is a core coating, and comprises at least one alkaline catalyst capable of promoting the ring-opening reaction of the epoxy resin; ii) a B component, wherein the B component is a coating shell comprising at least one crystalline solid unsaturated polyester resin or a semi-crystalline solid unsaturated polyester resin; iii) a C component, wherein the C component is a coating medium comprising at least one alkane wax.

[0051] In order to better explain this technical solution, this article defines some technical terms: "Room temperature" herein refers to 23°C.

[0052] "Normal temperature" herein refers to 23°C-35°C.

[0053] "Acceptably cured at low temperatures" means that the powder coating resists at least 100 double rubs of acetone when cured at temperatures of up to 110°C for up to 10 minutes.

[0054] "Good adhesion" in this context means that the adhesion of the powder coating is in the range of 0-2, more preferably in the range of 0-1, on a scale of 0 (best) to 5 (worst) according to the ISO 2409 cross cut test.

[0055] "Curing" in this article refers to the process in which the coating forms an irreversible cross-linked network after a chemical reaction, in which the material no longer flows, melts or dissolves, and "curing" and "cross-linking" are interchangeable in this article. The heat-curable powder coating of the present invention uses heat to cure, which is called "thermal curing", excluding curing caused by ultraviolet (UV), electron beam, thermal free radical initiators.

[0056] "Good leveling performance" in this article refers to the leveling performance of conventional powder coatings, which is divided into a grade range of 1 (worst leveling)-10 (best leveling). The leveling performance of a good powder coating needs to be equal to or higher than grade 3, more preferably equal to or higher than grade 4, even more preferably equal to or higher than grade 5, and most preferably equal to or higher than grade 6.

[0057] "Resin" herein can be understood to have the same meaning as understood by those skilled in the art of thermosetting polymer chemistry, a polymer having reactive groups that can be crosslinked by heat curing. The molecular weight of the resin can be characterized by the number average molecular weight (Mn) or the weight average molecular weight (Mw) well known to those skilled in the art of thermosetting polymer chemistry.

[0058] As used herein, "composition" refers to a combination and / or mixture of different chemical substances and / or components that form a whole.

[0059] "Powder" in this article refers to a fine, loose particle state, which does not clump at room temperature of 23°C-40°C and has good fluidity, and can be coated using a conventional electrostatic powder coating process; wherein the size of a single particle is at most 130 microns at room temperature and atmospheric pressure. The method used to measure the particle size of the granular material according to the present invention is a sieving method.

[0060] "Heat-curable powder coating" refers herein to a composition in powder form which has the ability to be cured by heating. The composition of the present invention is a heat-curable composition.

[0061] The term "slow-release coated heat-curable powder coating catalyst composition" herein refers to a composition of a catalyst for powders, which has the ability to catalyze the curing of powder coatings by heating.

[0062] "Unsaturated resin" herein refers to a resin containing ethylenically unsaturated groups.

[0063] "Powder coating" herein refers to a partially or fully cured form of the heat-curable powder coating of the present invention.

[0064] In addition, the glass transition temperature Tg, melting point (Tm), and crystallization temperature (Tc) described herein may be measured by differential scanning calorimetry (DSC).

[0065] Unless otherwise specified, "viscosity" in this article refers to the melt viscosity at 160°C (in Pa.s). Viscosity was measured using a rotational rheometer Brookfield CAP2000+, with a rotation speed of 200 rpm and a 5# rotor of 19.07 mm.

[0066] In a preferred embodiment, the slow-release coated heat-curable powder coating catalyst composition comprises: i) Component A, wherein the component A is a core coating, and comprises at least one alkaline catalyst capable of promoting the ring-opening reaction of epoxy resin at 70-130° C.; ii) a B component, wherein the B component is a coating shell comprising at least one crystalline solid unsaturated polyester resin or a semi-crystalline solid unsaturated polyester resin; iii) a C component, wherein the C component is a coating medium comprising at least one alkane wax.

[0067] Under room temperature dry storage conditions, the lower the curing temperature of the powder coating of the traditional polyester epoxy mixed reaction system, the easier it is to lose gloss. The powder coating cured below 120°C will lose gloss within 7 days. The present invention includes component A, component B, and component C, and realizes the coating of the alkaline catalyst of component A by the (semi-) crystalline olefinic unsaturated polyester resin solid of component B. At room temperature, the catalyst coated with the crystalline packaging material with a melting point higher than 50°C is physically isolated from the main components of the reaction and cannot participate in the chemical cross-linking reaction. It is unsealed and activated at a low temperature of 90°C, which is close to the melting point of the packaging material, and catalyzes the main chemical reaction of the ultra-low temperature powder coating at a temperature of 95-120°C. Therefore, under the premise of not affecting the low-temperature curing of the powder coating, the embodiment of the present invention can significantly extend the storage period of the ultra-low temperature powder coating at room temperature, meet the process requirements of normal powder coating, and solve the problem of traditional ultra-low temperature powder losing gloss within 7 days of storage. Preferably, the curing temperature of the powder coating of the present invention is 95-115°C, and more preferably 100-110°C.

[0068] Specifically, this embodiment uses the C component coating medium alkane wax and the B component (semi) crystalline solid polyester resin to coat the A component containing an alkaline catalyst that promotes the epoxy resin ring-opening reaction at 70-130°C, and the coating is achieved by utilizing the difference in miscibility caused by different molecular polarities.

[0069] First, the alkaline catalyst particles of component A are suspended and dispersed in the alkane wax of component C as a coating medium, so that the alkaline catalyst particles of component A are coated by component C; Then, the (semi)crystalline solid polyester resin of component B is melt-dispersed into the dispersed emulsion of components C and A. The different molecular polarities of the alkane wax of component C and the (semi)crystalline solid polyester resin of component B in the alkaline catalyst containing the ring-opening reaction of epoxy resin at 70-130°C are utilized to cause the difference in miscibility. The coating medium component C coated on the outer layer of component A is replaced by component B and is separated into two distinct phases by utilizing the difference in melting point and polarity, thereby achieving the purpose of coating and separation.

[0070] The components of the heat-curable powder coating catalyst composition of the present invention are further described below.

[0071] In some embodiments, the A component comprises at least one organic amine catalyst or organic phosphite catalyst that can promote the ring-opening reaction of epoxy resin, and its general structural formula is X(R)n, X is N or P element, R is the same or different alkyl, aryl or aralkyl containing 1-18 carbon atoms, and n can be the number 3 or 4.

[0072] Alternatively, the component A is an imidazole catalyst.

[0073] In some embodiments, the A component contains at least one anionic copolymer Lewis base catalyst that can promote the ring-opening reaction of the epoxy resin, and its general structural formula is X(R)nY, X is N or P element, R is the same or different alkyl, aryl or arylalkyl containing 1-18 carbon atoms, Y can be a halogen element chlorine (Cl) or bromine (Br); n can be the number 3 or 4.

[0074] In some embodiments, the A component comprises at least one organic onium salt catalyst that can promote the ring-opening reaction of the epoxy resin, such as DTMeAB, NBu4Br, NBu4Cl, PPh4Br, PPh4Cl, PPNCl and the like.

[0075] It should be noted that the A component may be of various types, as long as it can promote the ring-opening reaction of epoxy resin at a temperature of 70-130°C.

[0076] The average particle size of the A component is preferably 0.8-1.5 microns, specifically 0.8 microns, 0.9 microns, 1.0 microns, 1.1 microns, 1.2 microns, 1.3 microns, 1.4 microns, 1.5 microns, etc., but not limited thereto.

[0077] In some embodiments, the B component is a product of the reaction of a crystalline polyester or semi-crystalline polyester containing a carboxyl group with a methacrylic acid monomer and / or its derivatives, and its crystallinity can be measured using one or more of diacids and diols, wherein the diacids include but are not limited to succinic acid, adipic acid, sebacic acid, and dodecanedioic acid, and the diols include but are not limited to hexanediol, ethylene glycol, butanediol, and ethylene glycol.

[0078] In the present embodiment, the (semi)crystalline polyester resin generally refers to a polycondensation product of a polyol and a polyacid, preferably a polycondensation product of a dibasic acid, a diol (glycol) and / or a trifunctional alcohol, a trifunctional carboxylic acid. The polyacid is preferably a polycarboxylic acid, and the polycarboxylic acid includes but is not limited to isophthalic acid, terephthalic acid, phthalic acid, tetrahydrophthalic acid, hexahydroterephthalic acid, isophthalic acid, adipic acid, sebacic acid, succinic acid, trimellitic acid, 2-methyl-2-butenedioic acid, 2-butenedioic acid, itaconic acid and its derivatives, etc. These exemplary polyacids can be used in their acid form, or in the form of anhydride, acid chloride or lower alkyl ester, or in the form of a mixture of polyacids, and hydroxycarboxylic acids and lactones can also be used. Polyols can be subjected to polycondensation reaction with the above carboxylic acids and their derivatives to prepare polyester resins. Examples of polyols include, but are not limited to, aliphatic diols, 2,2-dimethylpropane-1,3-diol (neopentyl glycol), propane-1,2-diol, propane-1,3-diol, butane-1,3-diol, butane-1,2-diol, and 2,3-butanediol. The polyester resin can be prepared by a well-known esterification reaction and / or an ester exchange reaction. An organotin catalyst commonly used in esterification reaction can be used to adjust the ratio of COOH to OH to obtain the desired product polyester resin.

[0079] In this embodiment, the methacrylated unsaturated polyester resin is an unsaturated polyester containing an ethylenically unsaturated functional group with a methyl group, wherein the ethylenically unsaturated functional group is derived from a methacrylic acid monomer and a derivative thereof. In the methacrylated polyester resin, the ethylenically unsaturated functional group with a methyl group is generally located at the end of the unsaturated polyester resin. The methacrylated polyester resin can be prepared, for example, by first preparing a (semi) crystalline polyester intermediate using a common polyester manufacturing method, and then reacting the (semi) crystalline polyester intermediate with a methacrylic acid monomer and a derivative thereof to form an unsaturated polyester resin containing an ethylenically unsaturated functional group with a methyl group at the end.

[0080] In some embodiments, the B component satisfies at least one of the following conditions: a. The number average molecular weight Mn of the B component is 100-10000Da; b. The melting point of the B component is 50-120°C and the crystallization point is 40-90°C; c. The viscosity of the B component at a temperature of 100° C. is 0.01-20 Pa.s.

[0081] Furthermore, regarding the B component, at least one (semi)crystalline ethylenically unsaturated polyester resin is included, and its number average molecular weight Mn is at least 100 Da, preferably at least 500 Da, more preferably at least 1500 Da, and further preferably at least 2500 Da. The B component containing a (semi)crystalline ethylenically unsaturated polyester resin has a number average molecular weight Mn of at most 10000 Da, preferably at most 8000 Da, more preferably at most 5000 Da, and further preferably at most 4000 Da.

[0082] The B component comprising at least one (semi)crystalline ethylenically unsaturated polyester resin has a melting point of at least 50° C., preferably at least 55° C., more preferably at least 60° C., and further preferably 65° C. The B component comprising at least one (semi)crystalline ethylenically unsaturated polyester resin has a melting point of at most 120° C., preferably at most 110° C., more preferably at most 105° C., and further preferably at most 100° C.

[0083] The B component comprising at least one (semi)crystalline ethylenically unsaturated polyester resin has a viscosity at 100°C of at least 0.01 Pa.s, preferably at least 0.05 Pa.s, more preferably at least 0.1 Pa.s, and further preferably at least 0.5 Pa.s. The B component comprising at least one (semi)crystalline ethylenically unsaturated polyester resin has a viscosity at 100°C of at most 20 Pa.s, preferably at most 15 Pa.s, more preferably at most 10 Pa.s, further preferably at most 5 Pa.s, and particularly preferably at most 1 Pa.s.

[0084] In some embodiments, the C component comprises at least one linear alkane-containing paraffin.

[0085] In some embodiments, the C component contains at least one alkane wax containing 15-35 carbon atoms, preferably one or more of C16 alkanes, C18 alkanes, C22 alkanes, C28 alkanes, isomeric C20 alkanes, and cyclo C25 alkanes, but is not limited thereto.

[0086] In some embodiments, the C component comprises at least one alkane wax having a melting point of 30-70°C, more preferably an alkane wax having a melting point of 50-70°C.

[0087] Further, regarding the content of each component, the sum of the added amounts of component A, component B and component C is 100wt%; the added amount of component A is 20-60wt% of the total amount of component A, component B and component C; the added amount of component B is 30-70wt% of the total amount of component A, component B and component C; and the added amount of component C is 10-45wt% of the total amount of component A, component B and component C.

[0088] Preferably, regarding the content of each component, the sum of the added amounts of component A, component B and component C is 100wt%; the added amount of component A is 30-50wt% of the total amount of component A, component B and component C; the added amount of component B is 40-60wt% of the total amount of component A, component B and component C; the added amount of component C is 10-30wt% of the total amount of component A, component B and component C.

[0089] More preferably, regarding the content of each component, the sum of the added amounts of component A, component B and component C is 100wt%; the added amount of component A is 30-50wt% of the total amount of component A, component B and component C; the added amount of component B is 30-50wt% of the total amount of component A, component B and component C; the added amount of component C is 10-25wt% of the total amount of component A, component B and component C.

[0090] Correspondingly, such as Figure 2As shown, the present invention also discloses a method for preparing a slow-release coated heat-curable powder coating catalyst composition, comprising: S101, heating component C to make it melt completely and turn it into a liquid state; Preferably, the C component is heated to T1, and the melting point of the C component is T C , T1-T C =2°C~8°C. Further preferably, the C component is heated to T1, and the melting point of the C component is T C , T1-T C =4°C~6°C. More preferably, the C component is heated to T1, and the melting point of the C component is T C , T1-T C =5°C. In this step, component C is heated to T1 to melt it completely and obtain a uniform liquid.

[0091] S102, crushing component A; Preferably, component A is crushed to an average particle size of 0.1-5 microns. More preferably, component A is crushed to an average particle size of 0.8-1.5 microns.

[0092] In some embodiments, in this step, a supersonic pulverizer may be used to pulverize component A to a D50 of 0.1-5 microns, but the present invention is not limited thereto.

[0093] S103, adding the crushed component A to the liquid component C, stirring and mixing them evenly to obtain a first premix; The crushed component A is added to the liquid component C, and after being stirred evenly, a uniform first premix of emulsion liquid can be obtained. In this step, the alkaline catalyst particles of component A are suspended and dispersed in the alkane wax of the coating medium of component C, so that the alkaline catalyst particles of component A are coated by component C.

[0094] S104, heating the first premix to a temperature above the melting point of component B, adding component B to the first premix, and stirring to completely melt component B to obtain a second premix; Preferably, the first premix is ​​heated to T2, and the melting point of the B component is T B , T2-T B =12°C~20°C. Further preferably, the first premix is ​​heated to T2, and the melting point of the B component is T B , T2-T B =13°C~18°C. More preferably, the first premix is ​​heated to T2, and the melting point of the B component is T B , T2-T B =15℃.

[0095] In this step, the first premix is ​​heated to a temperature above the melting point of component B, and component B is added to the first premix and stirred to completely melt component B. The (semi) crystalline solid polyester resin of component B is melted and dispersed into the dispersed emulsion of component C and component A, and the molecular polarity difference between the alkane wax of component C coating medium and the (semi) crystalline solid polyester resin of component B is utilized to make the two completely incompatible, so that component B can be suspended and dispersed in the coating medium of component C, and the basic conditions required for coating are achieved.

[0096] S105, cooling the second premixture and stirring at a low speed until the C component forms two distinct layers, the upper phase is the separate C component, and the lower phase is the mixed phase of the B component covering the A component; Preferably, the second premix is ​​cooled to T3, and the melting point of the B component is T B , the melting point of the C component is T C , T3-T C =2℃~8℃, and T B -T3=12°C~20°C. Further preferably, the second premix is ​​cooled to T3, and the melting point of the B component is T B , the melting point of the C component is T C , T3-T C =3℃~6℃, and T B -T3=13°C~18°C. More preferably, the second premix is ​​cooled to T3, and the melting point of the B component is T B , the melting point of the C component is T C , T3-T C =5℃, and T B -T3=15℃.

[0097] The (semi)crystalline solid polyester resin of component B is melted and dispersed into the dispersed emulsion of components C and A. The different miscibility between components C and B with respect to the molecular polarity of the alkaline catalyst causes the coating medium component C coated on the outer layer of component A to be replaced by component B and separated into two distinct phases by utilizing the difference in melting point and polarity, thereby achieving the purpose of coating and separation.

[0098] S106, sucking out the upper phase, cooling and crushing; This step can suck out the upper phase and crush it into powder particles for reuse, thus improving environmental protection. The upper phase is mainly the coating medium C component, which is easy to separate and can be recycled and reused. The coating process is green and environmentally friendly, and no three waste substances are generated. It solves the problems of the coating medium in the common coating technology, such as complex separation, difficulty in reuse, and easy generation of wastewater and harmful organic matter.

[0099] S107, crushing the lower phase to obtain a sustained-release coated heat-curable powder coating catalyst composition.

[0100] Preferably, the lower phase is crushed to an average particle size of 0.5-5 microns to obtain a slow-release coated heat-curable powder coating catalyst composition. More preferably, the lower phase is crushed to an average particle size of 1-3 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

[0101] The sustained-release coated heat-curable powder coating catalyst composition is isolated from the main reaction components by the catalyst coated by the packaging material with a melting point higher than 50°C at room temperature, and cannot participate in the chemical cross-linking reaction, and has good stability. The catalyst composition is low-temperature unsealed and activated at a temperature close to the melting point of the packaging material at 90°C, and catalyzes the main chemical reaction of the ultra-low temperature powder coating at a temperature of 95-120°C. In addition, after the catalyst composition is melt-activated, the packaging material used to coat the catalyst is itself one of the main reaction resin components of the powder coating, and can participate in the chemical cross-linking reaction to form a cured coating.

[0102] Correspondingly, the present invention also provides a heat-curable powder coating, comprising the above-mentioned slow-release coated heat-curable powder coating catalyst composition; or, the slow-release coated heat-curable powder coating catalyst composition prepared by the above-mentioned preparation method.

[0103] A preferred embodiment of the heat-curable powder coating comprises a resin and a slow-release coated heat-curable powder coating catalyst composition.

[0104] The resin may be one or more of epoxy resin and polyester resin; The slow-release coated heat-curable powder coating catalyst composition is added in an amount of 1wt%-20wt%, and the resin is added in an amount of 80wt%-99wt%. Preferably, the slow-release coated heat-curable powder coating catalyst composition is added in an amount of 2wt%-15wt%, and the resin is added in an amount of 85wt%-98wt%. More preferably, the slow-release coated heat-curable powder coating catalyst composition is added in an amount of 3wt%-10wt%, and the resin is added in an amount of 90wt%-97wt%.

[0105] Another preferred embodiment of the heat-curable powder coating comprises a resin, a slow-release coated heat-curable powder coating catalyst composition, a filler, a pigment, and an additive.

[0106] The resin may be one or more of epoxy resin and polyester resin; The slow-release coated heat-curable powder coating catalyst composition is added in an amount of 1wt%-20wt%; the resin is added in an amount of 70wt%-98wt%; the filler is added in an amount of 0.1wt%-10wt%; the pigment is added in an amount of 0.1wt%-10wt%; and the auxiliary agent is added in an amount of 0.1wt%-10wt%.

[0107] Accordingly, the present invention also provides a method for preparing a heat-curable powder coating, comprising: Mixing a resin and a slow-release coated heat-curable powder coating catalyst composition to obtain a powder coating preliminary mixture; Melting and mixing the powder coating preliminary mixture, and cooling to room temperature to obtain a mixture; The cooled mixture is pulverized to obtain a powder coating.

[0108] Preferably, the powder coating preliminary mixture is melt mixed, which may be performed by melt extruding the powder coating preliminary mixture through an extruder, or by melt mixing through other methods for preparing powder coating.

[0109] See also Figure 1 , Figure 1 is a differential scanning calorimetry (DSC) graph of the heat-curable powder coating of the present invention, Figure 1 The heating curves under different heating rates are shown, including, from top to bottom, curve 1 is a heating curve with a heating rate of 3°C / min, curve 2 is a heating curve with a heating rate of 5°C / min, curve 3 is a heating curve with a heating rate of 8°C / min, and curve 4 is a heating curve with a heating rate of 10°C / min.

[0110] It can be seen from the DSC curve that the glass transition temperature (inflection point) of the present invention is 95-105°C, that is, the starting temperature of the reaction is 95-105°C, and the peak temperature of the reaction is 118-129°C. Therefore, the prepared powder coating can be desealed and activated at a low temperature of 90°C, which is close to the melting point of the packaging material, and catalyze the main chemical reaction of the ultra-low temperature powder coating at a temperature of 95-120°C for curing.

[0111] The present invention is further described below with specific embodiments Example 1 1. Formula: i) Component A, using an organic amine catalyst, with an amount of 20wt%; ii) Component B, which is a product of the reaction of a crystalline polyester or semi-crystalline polyester containing a carboxyl group with a methacrylic acid monomer and / or its derivatives, is used in an amount of 40 wt %, wherein component B is prepared by the following method: 192 g of ethylene glycol, 803 g of 1,12-dodecane diacid, 4100 catalyst (0.15 mmol), antioxidant (0.6 g) and water (4 g) were added to a four-necked bottle equipped with a thermometer, a stirrer and a distillation apparatus, and heated to 140°C under nitrogen protection to distill out water. The temperature was continued to rise to 220°C without releasing water, and the temperature was maintained at 220°C for vacuum polymerization to obtain an acid value of 56 mgKOH / g, a hydroxyl value of less than 3 mg KOH / g, and a number average molecular weight of Mn of 2000. The crystalline polyester is then cooled to 140°C, and a mixture of 112 g of glycidyl methacrylate, 5.6 g of ethyltriphenylphosphonium bromide, and 0.7 g of 2,5-di-tert-butyl-1,4-hydroquinone is slowly added dropwise under normal pressure, and the mixture is stirred and reacted at 140°C for 1 hour to obtain a final product, a methacrylic acid-terminated ethylenically unsaturated solid polyester resin, having a number average molecular weight of 2220, a viscosity of 200 mPa.s at 100°C, an acid value of 1.0 mg KOH / g, a melting point Tm of 75°C, and a hydroxyl value of 54 mg KOH / g.

[0112] iii) Component C, C16 alkane wax is selected, and the amount used is 40wt%.

[0113] (II) Preparation method: 1) Heat component C to a temperature 5 degrees above its melting point and keep it warm until it melts completely and turns into a liquid state; 2) Component A is crushed to D50 0.8-1.5 microns using a supersonic jet mill; 3) adding the crushed component A in step 2) to the liquid component C in step 1) and stirring and mixing them evenly to obtain a uniform emulsion as the first premix; 4) heating the first premix in step 3) to 15 degrees above the melting point of component B, adding component B to the first premix, stirring to ensure that component B is completely melted to form a uniform mixture, and obtaining a second premix; 5) Cooling the second premix in step 4) to 5 degrees above the melting point of component C and 15 degrees below the melting point of component B, stirring the second premix at a low speed while keeping the temperature high until component C forms two distinct layers and is completely sucked out: the upper phase is a transparent liquid component C alone, and the lower phase is a mixed phase of component B covering component A, to obtain a third premix; 6) sucking out the C component on the upper layer of the third premix in step 5), cooling it, and crushing it into powder particles for reuse; 7) The mixture in which the lower layer B component of the third premix in step 5) is coated with the A component is cooled and crushed to D501-3 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

[0114] Example 2 1. Formula: i) Component A, using anionic copolymerization Lewis base catalyst, the dosage is 35wt%; ii) Component B, which is a product of the reaction of a crystalline polyester or semi-crystalline polyester containing a carboxyl group with a methacrylic acid monomer and / or its derivatives, is used in an amount of 35 wt %, wherein component B is prepared by the following method: 192 g of ethylene glycol, 803 g of 1,12-dodecane diacid, 4100 catalyst (0.15 mmol), antioxidant (0.6 g) and water (4 g) were added to a four-necked bottle equipped with a thermometer, a stirrer and a distillation apparatus, and heated to 140°C under nitrogen protection to distill out water. The temperature was continued to rise to 220°C without releasing water, and the temperature was maintained at 220°C for vacuum polymerization to obtain an acid value of 56 mgKOH / g, a hydroxyl value of less than 3 mg KOH / g, and a number average molecular weight of Mn of 2000. The crystalline polyester is then cooled to 140°C, and a mixture of 112 g of glycidyl methacrylate, 5.6 g of ethyltriphenylphosphonium bromide, and 0.7 g of 2,5-di-tert-butyl-1,4-hydroquinone is slowly added dropwise under normal pressure, and the mixture is stirred and reacted at 140°C for 1 hour to obtain a final product, a methacrylic acid-terminated ethylenically unsaturated solid polyester resin, having a number average molecular weight of 2220, a viscosity of 200 mPa.s at 100°C, an acid value of 1.0 mg KOH / g, a melting point Tm of 75°C, and a hydroxyl value of 54 mg KOH / g.

[0115] iii) Component C: C18 alkane wax is selected, and the amount is 30wt%.

[0116] (II) Preparation method: 1) Heat component C to a temperature 6 degrees above its melting point and keep it warm until it melts completely and turns into a liquid state; 2) Component A is crushed to D50 0.8-1.5 microns using a supersonic jet mill; 3) adding the crushed group A in step 2) to the liquid component C in step 1) and stirring and mixing them evenly to obtain a uniform emulsion as the first premix; 4) heating the first premix in step 3) to 18 degrees above the melting point of component B, adding component B to the first premix, stirring to ensure that component B is completely melted to form a uniform mixture, and obtaining a second premix; 5) Cool the second premix in step 4) to 5 degrees above the melting point of component C and 15 degrees below the melting point of component B, keep the temperature and stir the second premix in step 4) at a low speed until component C forms two distinct layers and is completely sucked out: the upper phase is a transparent liquid component C alone, and the lower phase is a mixed phase of component B covering component A, to obtain a third premix; 6) sucking out the C component on the upper layer of the third premix in step 5), cooling it, and crushing it into powder particles for reuse; 7) The mixture in which the lower layer B component of the third premix in step 5) is coated with the A component is cooled and crushed to D501-3 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

[0117] Example 3 1. Formula: i) Component A, using an organic onium salt catalyst, with an amount of 50wt%; ii) Component B, which is a product of the reaction of a crystalline polyester or semi-crystalline polyester containing a carboxyl group with a methacrylic acid monomer and / or its derivatives, is used in an amount of 35 wt %, wherein component B is prepared by the following method: 192 g of ethylene glycol, 803 g of 1,12-dodecane diacid, 4100 catalyst (0.15 mmol), antioxidant (0.6 g) and water (4 g) were added to a four-necked bottle equipped with a thermometer, a stirrer and a distillation apparatus, and heated to 140°C under nitrogen protection to distill out water. The temperature was continued to rise to 220°C without releasing water, and the temperature was maintained at 220°C for vacuum polymerization to obtain an acid value of 56 mgKOH / g, a hydroxyl value of less than 3 mg KOH / g, and a number average molecular weight of Mn of 2000. The crystalline polyester is then cooled to 140°C, and a mixture of 112 g of glycidyl methacrylate, 5.6 g of ethyltriphenylphosphonium bromide, and 0.7 g of 2,5-di-tert-butyl-1,4-hydroquinone is slowly added dropwise under normal pressure, and the mixture is stirred and reacted at 140°C for 1 hour to obtain a final product, a methacrylic acid-terminated ethylenically unsaturated solid polyester resin, having a number average molecular weight of 2220, a viscosity of 200 mPa.s at 100°C, an acid value of 1.0 mg KOH / g, a melting point Tm of 75°C, and a hydroxyl value of 54 mg KOH / g.

[0118] iii) Component C: C22 alkane wax is selected, and the amount used is 15wt%.

[0119] (II) Preparation method: 1) Heat component C to a temperature 8 degrees above its melting point and keep it warm until it melts completely and turns into a liquid state; 2) Component A is crushed to D50 0.8-3 microns using a supersonic jet mill; 3) adding the crushed group A in step 2) to the liquid component C in step 1) and stirring and mixing them evenly to obtain a uniform emulsion as the first premix; 4) heating the first premix in step 3) to 20 degrees above the melting point of component B, adding component B to the first premix, stirring to ensure that component B is completely melted to form a uniform mixture, and obtaining a second premix; 5) Cool the second premix in step 4) to 5 degrees above the melting point of component C and 15 degrees below the melting point of component B, keep the temperature and stir the second premix in step 4) at a low speed until component C forms two distinct layers and is completely sucked out: the upper phase is a transparent liquid component C alone, and the lower phase is a mixed phase of component B covering component A, to obtain a third premix; 6) sucking out the C component on the upper layer of the third premix in step 5), cooling it, and crushing it into powder particles for reuse; 7) The mixture in which the lower layer B component of the third premix in step 5) is coated with the A component is cooled and crushed to D501-3 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

[0120] The slow-release coated heat-curable powder coating catalyst composition prepared in Examples 1-3 was tested for storage performance, and the results are shown in Table 1 below: Table 1 Test results of the powder coating catalyst compositions of Examples 1 to 3

[0121] Example 4 85 wt % of epoxy resin and 15 wt % of the sustained-release coated heat-curable powder coating catalyst composition obtained in Example 1 were mixed to obtain a powder coating preliminary mixture; The powder coating preliminary mixture is melt-extruded through an extruder and cooled to room temperature to obtain an extrudate; The cooled extrudate is pulverized to obtain a powder coating.

[0122] The powder coating prepared in Example 4 was sprayed on a medium density fiberboard (MDF) with a thickness of 15 mm using an electrostatic spray gun at a voltage of 60 kV. The sprayed MDF board was placed in an infrared oven with a set temperature of 120°C and an in-and-out time of 4 minutes. This was marked as sample 1.

[0123] The powder coating prepared in Example 4 was sprayed on a bamboo charcoal board with a thickness of 15 mm using an electrostatic spray gun, and the voltage was set to 50 kV. The sprayed bamboo charcoal board was placed in an infrared oven, and the temperature was set to 90° C. for 5.5 minutes. This was marked as Sample 2.

[0124] The powder coating prepared in Example 4 was sprayed on a 3 mm thick glass fiber reinforced plastic sample with an electrostatic spray gun at a voltage of 50 kV. The sprayed glass fiber reinforced plastic sample was placed in an infrared oven with a set temperature of 100°C and an in-and-out time of 4 minutes. This sample was labeled as Sample 3.

[0125] The above three samples were tested, and the test results are shown in Table 2 below: Table 2 Powder coating test results of Example 4

[0126] As shown in Table 2, the gelling time of the powder coating of Example 4 at 120°C is 59 seconds, the gelling time at 100°C is 80 seconds, and the gelling time at 90°C is 110 seconds. Therefore, the powder coating of this embodiment can be cured at 90-120°C. Other performance indicators, including gloss, hardness, adhesion, film forming properties (bubbles, dimensional deformation), etc., can meet the required performance of the coating.

[0127] Example 5 92 wt % of epoxy resin and 8 wt % of the slow-release coated heat-curable powder coating catalyst composition obtained in Example 2 were mixed to obtain a powder coating preliminary mixture; The powder coating preliminary mixture is melt-extruded through an extruder and cooled to room temperature to obtain an extrudate; The cooled extrudate is pulverized to obtain a powder coating.

[0128] The powder coating prepared in Example 5 was sprayed on a medium density fiberboard (MDF) with a thickness of 15 mm using an electrostatic spray gun at a voltage of 60 kV. The sprayed MDF board was placed in an infrared oven with a set temperature of 100°C and an in-and-out time of 4 minutes. This was marked as sample 1.

[0129] The powder coating prepared in Example 5 was sprayed on a bamboo charcoal board with a thickness of 15 mm using an electrostatic spray gun, and the voltage was set to 50 kV. The sprayed bamboo charcoal board was placed in an infrared oven, and the temperature was set to 90° C. for 5.5 minutes. This was marked as Sample 2.

[0130] The powder coating prepared in Example 5 was sprayed on a 3 mm thick glass fiber reinforced plastic sample with an electrostatic spray gun at a voltage of 50 kV. The sprayed glass fiber reinforced plastic sample was placed in an infrared oven with a set temperature of 100°C and an in-and-out time of 5 minutes. This sample was marked as Sample 3.

[0131] The above three samples were tested, and the test results are shown in Table 3 below: Table 3 Powder coating test results of Example 5

[0132] As shown in Table 3, the gelling time of the powder coating of Example 5 tested at 120°C is 63 seconds, the gelling time tested at 100°C is 85 seconds, and the gelling time tested at 90°C is 120 seconds. Therefore, the powder coating of this embodiment can be cured at 90-120°C. Other performance indicators, including gloss, hardness, adhesion, film forming properties (bubbles, dimensional deformation), etc., can meet the required performance of the coating.

[0133] Example 6 Mixing 95 wt % of epoxy resin and 5 wt % of the sustained-release coated heat-curable powder coating catalyst composition obtained in Example 3 to obtain a powder coating preliminary mixture; The powder coating preliminary mixture is melt-extruded through an extruder and cooled to room temperature to obtain an extrudate; The cooled extrudate is pulverized to obtain a powder coating.

[0134] The powder coating prepared in Example 6 was sprayed on a medium density fiberboard (MDF) with a thickness of 15 mm using an electrostatic spray gun at a voltage of 60 kV. The sprayed MDF board was placed in an infrared oven with a set temperature of 100°C and an in-and-out time of 4 minutes. This was marked as sample 1.

[0135] The powder coating prepared in Example 6 was sprayed on a bamboo charcoal board with a thickness of 15 mm using an electrostatic spray gun, and the voltage was set to 50 kV. The sprayed bamboo charcoal board was placed in an infrared oven, and the temperature was set to 90° C. for 5.5 minutes. This was marked as Sample 2.

[0136] The powder coating prepared in Example 6 was sprayed on a 3 mm thick glass fiber reinforced plastic sample with an electrostatic spray gun at a voltage of 50 kV. The sprayed glass fiber reinforced plastic sample was placed in an infrared oven with a set temperature of 100° C. and an in-and-out time of 5 minutes. This sample was labeled as Sample 3.

[0137] The above three samples were tested, and the test results are shown in Table 4 below: Table 4 Powder coating test results of Example 6

[0138] As shown in Table 4, the gelling time of the powder coating of Example 6 at 120°C is 70 seconds, the gelling time at 100°C is 95 seconds, and the gelling time at 90°C is 130 seconds. Therefore, the powder coating of this embodiment can be cured at 90-120°C. Other performance indicators, including gloss, hardness, adhesion, film forming properties (bubbles, dimensional deformation), etc., can meet the required performance of the coating.

[0139] It should be noted that the gloss is the glossiness of the coating surface measured at an incident angle of 60°.

[0140] Adhesion testing is based on GB9286, where 0-5 represents adhesion from good to bad. The specific grading standard is described as follows: 0-The cutting edge is completely smooth, without any peeling.

[0141] Pencil hardness is based on ASTM3363.

[0142] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A sustained-release coated heat-curable powder coating catalyst composition, characterized in that: include: i) Component A, wherein the component A is a core coating, and comprises at least one alkaline catalyst capable of promoting the ring-opening reaction of the epoxy resin; ii) a B component, wherein the B component is a coating shell comprising at least one crystalline solid unsaturated polyester resin or a semi-crystalline solid unsaturated polyester resin; iii) a C component, wherein the C component is a coating medium comprising at least one alkane wax.

2. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1, characterized in that: The A component comprises at least one basic catalyst which can promote the ring-opening reaction of the epoxy resin at 70-130°C.

3. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1 or 2, characterized in that: The component A comprises at least one organic amine catalyst, organic phosphorus salt catalyst or imidazole catalyst which can promote the ring-opening reaction of epoxy resin.

4. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1 or 2, characterized in that: The A component contains at least one anionic copolymerization Lewis base catalyst which can promote the ring-opening reaction of the epoxy resin.

5. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1 or 2, characterized in that: The A component contains at least one organic onium salt catalyst which can promote the ring-opening reaction of epoxy resin.

6. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1 or 2, characterized in that: The average particle size of the A component is 0.8-1.5 microns.

7. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1, characterized in that: The B component is a product of a reaction between a crystalline polyester or a semi-crystalline polyester containing a carboxyl group and a methacrylic acid monomer and / or a derivative thereof.

8. The sustained-release coated heat-curable powder coating catalyst composition according to claim 7, characterized in that: The B component meets at least one of the following conditions: a. The number average molecular weight Mn of the B component is 100-10000Da; b. The melting point of the B component is 50-120°C and the crystallization point is 40-90°C; c. The viscosity of the B component at a temperature of 100° C. is 0.01-20 Pa.s.

9. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1, characterized in that: The C component comprises at least one straight-chain paraffin wax.

10. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1, characterized in that: The C component comprises at least one alkane wax containing 15 to 35 carbon atoms.

11. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1, characterized in that: The C component comprises at least one alkane wax having a melting point of 30-70°C.

12. The sustained-release coated heat-curable powder coating catalyst composition according to claim 1, characterized in that: The total amount of component A, component B and component C added is 100wt%; The amount of component A added is 20-60wt% of the total amount of component A, component B and component C; The amount of component B added is 30-70wt% of the total amount of component A, component B and component C; The added amount of the C component is 10-45 wt % of the total amount of the A component, the B component and the C component.

13. A method for preparing a sustained-release coated heat-curable powder coating catalyst composition according to any one of claims 1 to 12, characterized in that: include: Heat component C to make it melt completely and turn it into a liquid state; Crush component A; Adding the crushed component A to the liquid component C, stirring and mixing evenly to obtain a first premix; The first premix is ​​heated to a temperature above the melting point of component B, component B is added to the first premix, and stirred to completely melt component B to obtain a second premix; The second premix is ​​cooled and stirred at a low speed until the C component forms two distinct layers, the upper phase is the separate C component, and the lower phase is the mixed phase of the B component covering the A component; The upper phase is sucked out, cooled and crushed; The lower phase is pulverized to obtain a slow-release coated heat-curable powder coating catalyst composition.

14. The method for preparing the sustained-release coated heat-curable powder coating catalyst composition according to claim 13, characterized in that: The C component is heated to T1, and the melting point of the C component is T C , T1-T C =2℃~8℃.

15. The method for preparing the sustained-release coated heat-curable powder coating catalyst composition according to claim 13, characterized in that: Component A is crushed to an average particle size of 0.1-5 microns.

16. The method for preparing the sustained-release coated heat-curable powder coating catalyst composition according to claim 15, characterized in that: Component A is crushed to an average particle size of 0.8-1.5 microns.

17. The method for preparing the sustained-release coated heat-curable powder coating catalyst composition according to claim 13, characterized in that: The first premix is ​​heated to T2, the melting point of the B component is T B , T2-T B =12℃~20℃.

18. The method for preparing the sustained-release coated heat-curable powder coating catalyst composition according to claim 13, characterized in that: The second premix is ​​cooled to T3, and the melting point of the B component is T B , the melting point of the C component is T C , T3-T C =2℃~8℃, and T B -T3=12℃~20℃.

19. The method for preparing a sustained-release coated heat-curable powder coating catalyst composition according to claim 13, characterized in that: The lower phase is crushed to an average particle size of 0.5-5 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

20. The method for preparing the sustained-release coated heat-curable powder coating catalyst composition according to claim 19, characterized in that: The lower phase is crushed to an average particle size of 1-3 microns to obtain a slow-release coated heat-curable powder coating catalyst composition.

21. A heat-curable powder coating, characterized in that A sustained-release coated heat-curable powder coating catalyst composition comprising any one of claims 1 to 12; Alternatively, a sustained-release coated heat-curable powder coating catalyst composition prepared by the preparation method according to any one of claims 13 to 20.

22. The heat-curable powder coating according to claim 21, characterized in that Also includes resin; The resin is selected from one or more of epoxy resin and polyester resin.

23. The heat-curable powder coating according to claim 21, characterized in that The slow-release coated heat-curable powder coating catalyst composition is added in an amount of 1wt%-15wt%; The added amount of the resin is 85wt%-99wt%.

24. The heat-curable powder coating according to claim 21, characterized in that It also contains one or more of fillers, pigments and additives.

25. A method for preparing a heat-curable powder coating according to any one of claims 21 to 24, characterized in that: include: Mixing a resin and a slow-release coated heat-curable powder coating catalyst composition to obtain a powder coating preliminary mixture; Melting and mixing the powder coating preliminary mixture, and cooling to room temperature to obtain a mixture; The cooled mixture is pulverized to obtain a powder coating.

26. The method for preparing a heat-curable powder coating according to claim 25, characterized in that: Melting and mixing the powder coating premix comprises: The powder coating preliminary mixture is melt-extruded through an extruder.

Citation Information

Patent Citations

  • Thermosetting powder coating composition and preparation method thereof

    CN112457751A

  • Single-component platinum catalyst and application thereof in manufacturing of silicone rubber synthetic leather

    CN114931944A

  • Magnetic prepreg of PCB (printed circuit board) of planar transformer and preparation method of magnetic prepreg

    CN115175446A

  • Thermally conductive adhesive compositions, methods of making and uses thereof

    CN117980427A

  • Coating powders, methods of manufacture thereof, and articles formed therefrom

    US20030194560A1

Cited By

  • Auxiliary agent for low-temperature curing powder coating and preparation method of auxiliary agent

    CN122609094A

  • An adjuvant for low temperature curing powder coatings and a method for its preparation

    CN122609094B